What Influences the Growth of Organic Farms? Evidence from a Panel of Organic Farms in Germany - Thelma Brenes-Mun\~oz; Sebastian Lakner; Bernhard Brum̈mer (German Journal of Agricultural Economics (GJAE), 2016)
Organic farming is one of the fastest-growing branches of agriculture in Germany. The net increase in the number of hectares comes partly from the conversion of conventional farms, but also in part from the acreage expansion of existing organic farms. So far, empirical research has focused on analysing conversion to organic farming, and lately on reversion to conventional farming. However, changes in individual organic farm sizes have remained ignored by empirical researchers. Additionally, the occurrence and the extent of farm growth are largely dependent on the regional conditions of land market, farm structure and policy measures. Therefore, it remains unclear what other factors besides increasing demand for organic products might influence growth of organic farms. The main objective in this study is to determine whether organic farms are changing their scale of operation and, if so, which factors contribute to - or stagnate - farm growth and to what extent. To answer these questions we analyse growth in a unique panel dataset of 453 farms over the 1993-2005 period using the system generalised method of moments estimator (SGMM). The results reveal that all farms increase area by a maximum of 10 ha and large farms change farm size more frequently than smaller ones. Increases in organic area are influenced by subsidies for organic farming and intensity of livestock production. Farm growth measured in terms of output is affected by farm size, land, capital, soil quality, and intensity of livestock production. – – (...) Das Ziel dieser Studie ist eine Untersuchung der zwei unterschiedlichen Wachstumsdimensionen landwirtschaftliche Nutzfläche und landwirtschaftlicher Umsatz sowie die Bestimmung der Faktoren, die das Wachstum - oder die Stagnation - auf Ökobetrieben beeinflussen Wir analysieren einen Panel-Datensatz mit 453 Betrieben zwischen 1993 und 2005 mit Hilfe eines 'System Generalised Methods of Moments (GMM)'-Schätzer. Die Ergebnisse zeigen, dass die Zuwächse bei ökologisch bewirtschafteter Fläche bei maximal 10 ha liegen. Die großen Betriebe ändern hierbei häufiger ihre Betriebsgröße als kleine Betriebe. Das Flächenwachstum von Ökobetrieben ist beeinflusst von Agrarumweltzahlungen und der Intensität der Tierhaltung. Auf das Umsatzwachstum der Ökobetriebe wirken die Betriebsgröße, Fläche, Kapital, Bodenqualität sowie die Intensität der Tierhaltung (Quelle: Verlag).
Keywords: 330